EMOTION RELEASING PROCESS AS A NEW APPROACH TO EASE UNCOMFORTABLE EMOTION: A CASE SERIES - Ardian, Jiemi (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2024)
Introduction – This paper explores the potential of the Emotion Releasing Process (ERP) as a therapeutic approach for individuals suffering from anxiety and depression, often stemming from traumatic memories. This case series aims to describe two cases using ERP as a therapeutic approach for individuals dealing with anxiety and depression. Methods – The study investigates the effectiveness of ERP through case series analyses of two individuals experiencing significant emotional distress. Results – Both cases demonstrated substantial reductions in anxiety and depression symptoms (56.25% and 93.75% decrease in HSCL scores) following a single ERP session. The paper highlights the unique strengths of ERP compared to traditional methods like CBT and psychodynamics, emphasizing its focus on directly addressing emotional sensations in the body rather than cognitive restructuring or storytelling. Discuss – Traumatic memories are different from ordinary memories in several ways. The emotional impact of traumatic memories can be significant. In addition to the emotional impact of traumatic memories, they can also have physical effects on the body. Conclusion - This approach, bypassing the need for detailed memory recall, holds promise for individuals struggling to verbalize or confront traumatic experiences. Further research is encouraged to explore the broader applications of ERP across various diagnoses and specific trauma types such as PTSD or complex trauma. Keywords: ERP, emotion, trauma, psychotherapy